Food security and food safety in the Mediterranean - Scoullos M.J.; Tomassini B. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
The present paper is focusing mainly on two issues : in the first part, on the interconnection between food security, food production, environmental conditions and needed natural resources (among which water is crucial), as well as on trade and in particular on the impacts of the Euro-Mediterranean free trade area. On the second part, the emphasis is given to the examination of the status of women in certain Mediterranean countries for which data is already available.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)